Epigenetic modifications and targeted therapy in pediatric acute myeloid leukemia - Huan Xu; Yuxi Wen; Runming Jin; Hongbo Chen (Frontiers Media S.A., 2022)
Acute myeloid leukemia (AML) is a hematological malignancy resulting from the genetic alterations and epigenetic dysregulations of the hematopoietic progenitor cells. One-third of children with AML remain at risk of relapse even though outcomes have improved in recent decades. Epigenetic dysregulations have been identified to play a significant role during myeloid leukemogenesis. In contrast to genetic changes, epigenetic modifications are typically reversible, opening the door to the development of epigenetic targeted therapy. In this review, we provide an overview of the landscape of epigenetic alterations and describe the current progress that has been made in epigenetic targeted therapy, and pay close attention to the potential value of epigenetic abnormalities in the precision and combinational therapy of pediatric AML.